A Visual Astronomer's Photographic Guide to the Deep Sky A Pocket Field Guide - Rumistrzewicz, Stefan. (Astronomer's Pocket Field Guide, 2010)
How many times have you found a deep sky object (DSO), ticked it off the list, and moved on, or used the Tour function on your GO-TO scope and said, Oh thats a just a smudge or Cant see it Ill move on to the next one. If this has happened to you, then this book is for you. It will challenge you to go back to the smudge and really look. Can you see the faint wisp or the detail in the southeastern corner? Can you see the small cluster within the cluster? Try to classify the open cluster for yourself. Compare it to the accepted Trumpler classification. Whether you have a GO-TO scope or not, this book gets you to rediscover one of the great things that got you into this hobby in the first place looking through the eyepiece of a telescope. So pack away the DSLR, CCD camera, the guide scope, and laptop and open your pencil case! Youre in for some fun!